EFFECT OF FENUGREEK SEEDS ON SOME PHYSIOLOGICAL CHARACTERS IN BROILER BREEDERS MALES - S. Y. Abdul-Rahman (Mesopotamia Journal of Agriculture)
This study aimed to investigate the effects of Fenugreek seeds treatment ( Trigonella foenum graecum ) on blood parameters of broiler breeder males , the study include 4 groups ( 9 Arbor Acres cock , each ) 65 weeks aged , 1group : Control: reared on standard ration. 2- The 1st : reared on standard ration ,supplemented 10 gm / kg ration once weekly 2- The 2nd : reared on standard ration, supplemented 10 gm / kg ration twice weekly .4- The 3rd: reared on standard ration, supplemented 10 gm / kg ration daily. The treatment continue for 8 weeks .Fenugreek seeds improve blood picture as compared with control represented by the significant increase in the RBCs ( 2.55 and 2.92 million / mm3 ) and hemoglobin concentration ( 12.51 and 14.43 gm /dl ) and PCV ( 31.8 and 34.26 % ) in the2nd and 3rd group , also a significant increase in the thrombocytes count ( 15002 , 17272 and 21553 / mm3 ) in the 1st, 2nd and 3rd groups , this was reflected on the significant reduction of the clotting time in the 3rd group ( 53.33 seconds ) , treatment has no effects on the T.WBC , on the other hand , there was a significant decrease in the Hetrophils % in the2nd and 3rd groups ( 23 % and 19.44 % ) , a significant increase in lymphocytes % in the 3rd group ( 72.33 % ) and a significant decrease in the Hetrophils : Lymphocytes in the3rd and 2nd groups( 34.0 and 26.44 % ) . Treatment also causes a significant decrease in serum glucose levels in the 2nd and 3rd groups ( 264.02 and 229.01 mg/dl ), cholesterol level in the 3rd ( 134.71mg/dl ) and triglycerides level in the 1st ,2nd and 3rd groups ( 160.88 and 150.84 and 120.38 mg / 100 ml ) respectively . In general , the study revealed that Fenugreek seeds improve some blood characters in advance aged broiler breeder males.